Growth, yield and quality of onion (Allium cepa L.) under different levels of irrigation and NPK-fertigation - PRADHAN, P.C.; BEHERA, S.; DEVI, S.; DASH, D.K. (Journal of Soil and Water Conservation, 2022)
The production, productivity and quality of produce are greatly influenced by the method of irrigation and fertilizer application. Being a shallow rooted crop, onion also prefers a light but frequent irrigation and also prefers a heavy nutrient. Keeping this in view, experiments were conducted for three consecutive years in randomized block design with ten treatments replicated thrice at Bhubaneswar. The treatments comprises of three levels of irrigation (100% ETc, 80% ETc and 60% ETc), three levels of NPK fertigation (100% Recommended dose of fertilizers, 80% RDF and 60% RDF) and compared with soil application of fertilizers and drip irrigation. Results revealed that integrated use of irrigation water and fertilizers at different levels found to be better over soil application of fertilizers and drip irrigation in growth and yield of onion (var. Agrifound Light Red). Application of irrigation at 80% ETc and fertigation of 100% RDF through drip irrigation resulted highest yield of onion (25.96 t ha-1) but at par with treatment having irrigation at 80% ETc and fertigation of 80% RDF (25.47 t ha-1). Considering the productivity and economic use of inputs like water and fertilizers, the treatment with irrigation of 80% ETc and 80% RDF fertigation was adjudged to be best water and nutrient management practice for onion cultivation in Odisha.